Exploring Career Capital of International Qualified Nurses Following an Adaptation Program in Malta - Neville Schembri (European Scientific Journal, ESJ, 2024)
Aim: The aim of the research was to explore the individual human, social and motivational capital of international qualified nurses seeking work opportunities as qualified nurses in Malta.Design: Qualitative research using a phenomenological approach.Methods: This study conducted adopting a qualitative methodology using semi structured focus group interviews with sixteen participants following a pre-registration nurse adaptation program delivered at Institute of Applied Sciences within Malta College of Arts, Science and Technology. Data analysis was conducted using Thematic Analysis.Results: From analysis of the data four main themes emerged, these were: importance of past experiences; training and education; decisions to leave home country and support from community or colleagues.Conclusion: The findings show that these nurses already possess a considerable degree of career capital. This need be taken into consideration when it comes to deployment and work opportunities to preserve skills and enhance job satisfaction and retention.